2006
DOI: 10.1038/sj.ijo.0803284
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity action of peripheral exenatide (exendin-4) in rodents: effects on food intake, body weight, metabolic status and side-effect measures

Abstract: Background: Exenatide (exendin-4) is an incretin mimetic currently marketed as an antidiabetic agent for patients with type 2 diabetes. In preclinical models, a reduction in body weight has also been shown in low-fat-fed, leptin receptor-deficient rodents. Objective: To more closely model the polygenic and environmental state of human obesity, we characterized the effect of exenatide on food intake and body weight in high-fat-fed, normal (those with an intact leptin signaling system) rodents. As glucagon-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
88
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 42 publications
(72 reference statements)
15
88
1
Order By: Relevance
“…The vagally transmitted effects of peripheral GLP-1R stimulation therefore involve behavioral and autonomic effector pathways that are downstream of CNS processing. [17][18][19]21,25 Structures in the ascending visceral afferent pathway, which includes nuclei of the caudal brainstem (NTS; parabrachial nucleus), hypothalamus (lateral hypothalamus; paraventricular nucleus) and basal forebrain (bed nucleus of stria terminalis; central nucleus of the amygdala), 26,27 may therefore play a role in mediating responses triggered by peripheral GLP-1R agonist treatmentA role. Similarly for the central GLP-1 system, direct central GLP-1R ligand administration activates neurons in many of the same central structures that show GLP-1-binding 23 and/or express GLP-1R mRNA.…”
Section: Glp-1mentioning
confidence: 99%
“…The vagally transmitted effects of peripheral GLP-1R stimulation therefore involve behavioral and autonomic effector pathways that are downstream of CNS processing. [17][18][19]21,25 Structures in the ascending visceral afferent pathway, which includes nuclei of the caudal brainstem (NTS; parabrachial nucleus), hypothalamus (lateral hypothalamus; paraventricular nucleus) and basal forebrain (bed nucleus of stria terminalis; central nucleus of the amygdala), 26,27 may therefore play a role in mediating responses triggered by peripheral GLP-1R agonist treatmentA role. Similarly for the central GLP-1 system, direct central GLP-1R ligand administration activates neurons in many of the same central structures that show GLP-1-binding 23 and/or express GLP-1R mRNA.…”
Section: Glp-1mentioning
confidence: 99%
“…Post hoc Bonferroni test was used for time to time analysis between the two treatment groups (*Po0.05, **Po0.01, ***Po0.001). 21,24,25 and humans. 26,27 The novel finding of this study is that food intake after gastric bypass can be altered by pharmacological doses of gut hormones or gut hormone analogues.…”
mentioning
confidence: 99%
“…[35][36][37][38][39] In this study, we found excessive abnormal lipid accumulation in the renal tissue of SHR-HF animals compared with that in WKY-HF groups, which was related to increases in the mesangial matrix, TGF-b1 expression, apoptotic glomerular cells and the infiltration of inflammatory cells into kidneys. These findings are consistent with those of previous studies showing that lipid accumulation in kidneys promotes glomerulosclerosis through the low-density lipoprotein-receptor in mesangial cells, through macrophage chemotaxis, increased production of fibrotic cytokines and direct podocyte injury through oxidative stress.…”
Section: Discussionmentioning
confidence: 92%